Compressive strength of lightweight foamed concrete using artificial aggregate from palm oil clinker - Akmal Hakim, Muhammad Sha'ani (2012)
Malaysia as one of the world's largest exporter of palm oil has been facing problem in disposing palm oil clinker, a by-product of palm oil mill since many years ago. Through public concerns and research efforts, the agro waste by-product materials have potential to be utilized as construction material to replace conventional sand in lightweight foamed concrete (L WC). In this study, the effectiveness of agro waste ash by-product namely palm oil clinker (POC) was developed as an alternative material to replace the sand. The effect of using different percentages of POC to L WC due to compressive strength was investigated. Five series of mix formulation of L WC with mix density of 1600kg/m3 were prepared that comprise of 0%, 25%, 50%, 75% and 100% as sand replacement from the total weight of sand was replaced with POC. All the L WC samples are cured in air curing for different curing ages namely 7, 28 and 60 days. The result revealed that the higher compressive strength was achieved through the addition of POC. The compressive strength also improved due to increasing of curing days. It is noted that the optimal mix to produce the highest compressive strength is by replacing 75% sand with POC.